1991
DOI: 10.1507/endocrj1954.38.627
|View full text |Cite
|
Sign up to set email alerts
|

Lack of PTC Gene(ret Proto-oncogene Rearrangement) in Human Thyroid Tumors.

Abstract: PTC gene, which is derived from the rearranged form of the ret proto-oncogene, was originally discovered in human thyroid papillary carcinomas. This gene has been thought to act as a tumorigenetic factor in thyroid carcinoma, although the action of PTC oncogene products is still unknown. To study the frequency of the PTC gene present in human thyroid carcinomas, we investigated four cell lines derived from thyroid carcinoma and 22 thyroid tumor tissue specimens. The reverse transcriptase-polymerase chain react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 11 publications
1
19
0
Order By: Relevance
“…The most common techniques include Southern blotting, direct gel visualization of the RT-PCR amplicons and hybridization of blotted RT-PCR products. Meta-analysis of the data published worldwide over a greater than 10-year period (Table 3) demonstrates an average prevalence of 18% for Southern blotting (67/370 cases tested, range 0-33%), [26][27][28][29][30][31] 15% for direct visualization of the RT-PCR amplicons (47/309 cases tested, range 4-45%) 7,32-35 and 48% for hybridization of blotted RT-PCR products (153/314 cases tested, range 0-85%). 4,[21][22][23][36][37][38][39] Allowing for the fact that Southern blotting permits the identification of all RET/PTC variants while the cases analyzed by RT-PCR listed above only screened the tumors for RET/PTC1, -2 and -3, there is a good correspondence between the sensitivity of Southern blotting and of direct gel visualization of RT-PCR products, as also demonstrated by parallel analysis of the same samples with the two methods.…”
Section: Discussionmentioning
confidence: 99%
“…The most common techniques include Southern blotting, direct gel visualization of the RT-PCR amplicons and hybridization of blotted RT-PCR products. Meta-analysis of the data published worldwide over a greater than 10-year period (Table 3) demonstrates an average prevalence of 18% for Southern blotting (67/370 cases tested, range 0-33%), [26][27][28][29][30][31] 15% for direct visualization of the RT-PCR amplicons (47/309 cases tested, range 4-45%) 7,32-35 and 48% for hybridization of blotted RT-PCR products (153/314 cases tested, range 0-85%). 4,[21][22][23][36][37][38][39] Allowing for the fact that Southern blotting permits the identification of all RET/PTC variants while the cases analyzed by RT-PCR listed above only screened the tumors for RET/PTC1, -2 and -3, there is a good correspondence between the sensitivity of Southern blotting and of direct gel visualization of RT-PCR products, as also demonstrated by parallel analysis of the same samples with the two methods.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is known that the rearrangement of RET gene is found in 35% of papillary carcinomas in general western population and occurs at much higher frequency in patients with a history of radiation exposure, with some reports even suggesting that radiation might induce Pax8-PPARg rearrangement [13,15]. However, the low frequency (0%-9%) of RET rearrangement in papillary carcinomas in Japan [21][22][23] and the inability to detect Pax8-PPARg fusion gene may be due to the relatively fewer patients treated with radiation therapy in this country. Therefore, the tumorigenesis of FTC in Japanese patients may be dependent mainly on other genetic factors such as Ras mutations which were found in 18%-52% of follicular carcinoma and were not found to overlap with Pax8-PPARg rearrangement in the molecular pathways of FTC [13].…”
Section: Discussionmentioning
confidence: 99%
“…The ret/ PTC1 oncogene is generally the most frequent form of RET rearrangement found in Caucasian populations, although the precise frequency varies with different studies (Jhiang et al 1992;Santoro et al 1992;Williams et al 1996;Bounacer et al 1997). In Japan, Namba et al (1991) examined ten papillary thyroid carcinomas only for ret/PTC1 rearrangements and found no rearrangement; Ishizaka et al (1991) found one ret/PTC1 rearrangement among 11 carcinomas, and Wajjwalku et al (1992) found only one such alteration among 38 carcinomas. On the basis of those observations, RET gene rearrangements in papillary thyroid carcinomas were thought to be rare in the Japanese population.…”
Section: Short Horizontal Bars Represent Hybridization Probes (Probesmentioning
confidence: 99%
“…These phenomena have seldom been detected in papillary thyroid carcinomas (less than 3%) in Japan, although until now Japanese investigators have examined this type of carcinoma only for the ret/PTC1 chimeric gene (Namba et al 1991;Wajjwalku et al 1992). The discrepancy in the reported frequency of ret/PTC oncogenes could be due to environmental, racial, or methodological factors.…”
Section: Introductionmentioning
confidence: 99%